Loss of Functional NADPH Oxidase 2 Protects Against Alcohol‐Induced Bone Resorption in Female p47phox−/− Mice. (20th November 2013) - Mercer, Kelly E.; Sims, Clark R.; Yang, Carrie S.; Wynne, Rebecca A.; Moutos, Christopher; Hogue, William R.; Lumpkin, Charles K.; Suva, Larry J.; Chen, Jin‐Ran; Badger, Thomas M.; Ronis, Martin J. J.
<x xml:space="preserve">Abstract</x> Background In bone, NADPH oxidase (NOX)‐derived reactive oxygen species (ROS) superoxide and/or hydrogen peroxide are an important stimulus for osteoclast differentiation and activity. Previously, we have demonstrated that chronic ethanol (EtOH) consumption generates excess NOX‐dependent ROS in osteoblasts, which functions to stimulate nuclear factor kappa‐β receptor ligand (RANKL)–RANK signaling, thus increasing osteoclastogenesis and activity. This activity can be blocked by co‐administration of EtOH with the pan‐NOX inhibitor diphenylene idonium (DPI). Methods To test whether EtOH‐induced bone loss is dependent on a functional NOX2 enzyme, 6‐week‐old female C57BL/6J‐Ncf1/p47phox−/− (p47phox KO) and wild‐type (WT) mice were pair‐fed EtOH diets for 40 days. Bone loss was assessed by 3‐point bending, micro‐computed tomography and static histomorphometric analysis. Additionally, ST2 cultured cells were co‐treated with EtOH and NOX inhibitors, DPI, gliotoxin, and plumbagin, after which changes in ROS production, and in RANKL and NOX mRNA expression were analyzed. Results In WT mice, EtOH treatment significantly reduced bone density and mechanical strength, and increased total osteoclast number and activity. In EtOH‐treated p47phox KO mice, bone density and mechanical strength were completely preserved. EtOH p47phox KO mice had no changes in osteoclast numbers or activity, and no elevations in serum CTX or RANKL gene expression (p < 0.05). In both WT and p47phox KO mice, EtOH feeding reduced biochemical markers of bone formation (p < 0.05). In vitro EtOH exposure of ST2 cells increased ROS, which was blocked by pretreating with DPI or the NOX2 inhibitor gliotoxin. EtOH‐induced RANKL and NOX2 gene expression were inhibited by the NOX4‐specific inhibitor plumbagin. Conclusions These data suggest that NOX2‐derived ROS is necessary for EtOH‐induced bone resorption. In osteoblasts, NOX2 and NOX4 appear to work in tandem to increase RANKL expression, whereas EtOH‐mediated inhibition of bone formation occurs via a NOX2‐independent mechanism.